Genetic polymorphism in 5’UTR of myostatin (MSTN) gene in Nilagiri sheep - Sahu, Amiya Ranjan; V Jeichitra; R Rajendran; A Raja (Journal of Livestock Biodiversity, 2025)
The study was undertaken to detect the genetic variation in the part of 5’UTR, exon 1 and part of intron 1 (797 bp) of MSTN gene in Nilagiri breed of sheep by Tetra-primer ARMS PCR. Randomly, eight samples of the PCR product were sent for sequencing. The analysis revealed the presence of SNP at 711 C>A in 5’UTR of MSTN gene. The identified SNP was genotyped by Tetra-primer ARMS-PCR. The C711A locus of MSTN gene is characterized by the higher frequency of allele “C” in this breed. The effect of mutation in this gene with growth traits were analysed by association study using least-squares and had no significant effect on growth traits.